PERKEMBANGAN AKTIVITAS OLAHRAGA SENAM AEROBIK DALAM MENINGKATKAN KEBUGARAN MASYARAKAT KOTA SURAKARTA - Jayanti, Karlina Dwi (Gelanggang Pendidikan Jasmani Indonesia, 2018)
The research used by researchers is descriptive qualitative research. This research uses survey model. the research is conducted on only one target (one location or one subject) for example, although research is conducted in several locations (multiple groups or a number of individuals). That is with the stages of observation, interview, documentation, data analysis. In this case study, the study used purposive sampling and snowball sampling techniques. For the determination of the research sample is done by purposive because it is known characteristics. The results of the research analysis showed that: 1. The development of aerobic gymnastics in Surakarta developed well with the container that shaded in aerobic gymnastics that is FORMI, and already many types of aerobic exercises that are taught among others zumba, BL, poco-poco etc. 2. Community participation in aerobic gymnastics is so supported by the community, one of them aerobic exercise is an alternative exercise that can be done to keep improving healthy life, because aerobic exercise is very easy to find everywhere. 3. The role of government in developing aerobic gymnastics is to provide broad access for public aerobic aerobics activities in public open spaces, as well as CFD events and government cooperation with private parties in terms of gymnastics competitions and aerobic gymnastics activities to always develop aerobic exercises .Keywords: Aerobic aerobics, development, government role